ANALISIS PENYUSUNAN LAPORAN KEUANGAN PADA YAYASAN PENDIDIKAN SMP SWASTA 17 AGUSTUS DESA TIGA JUHAR KECAMATAN STM HULU KABUPATEN DELI SERDANG - Mery Pramita Br Tarigan; Suhariyanti Suhariyanti (Worksheet : Jurnal Akuntansi, 2022)
Financial reports are the result of the accounting process, and are one of the most important information for organizations that describe organizational activities in a certain period and for decision making for the organization. The financial statements of non-profit entity organizations such as foundations must follow the guidelines for preparing financial statements in ISAK 35. This research was conducted at the 17 August Private Middle School Foundation, Tiga Juhar Village, STM Hulu District, Deli Serdang Regency. In this study the data used were the financial reports belonging to the 17 August 2020 Private Middle School Education Foundation. The data collection technique in this study was through direct interviews with relevant sources and knowing how to prepare financial reports at the August 17 Private Middle School Education Foundation, documentation by collecting documents in the form of photos, as well as reviewing the literature by studying reading sources (literature) related to the research. The results of the study show that the financial reports belonging to the August 17 Private Middle School Education Foundation are not yet effective and efficient, and are not in accordance with ISAK 35 guidelines.